TO STUDY THE DEPENDENCE OF THE INTENSITY OF "ABSOLUTE BLACK MATTER " RADIATION ON TEMPERATURE AND DISTANCE - Boydedayev Sobirjon Rahimjonovich; Umaraliyev Maksud Mahmudovich; Turgunov Adham Rakhmatillayevich (Galaxy International Interdisciplinary Research Journal, 2021)
Using the 1.Mall thermocouple, the relative intensity of radiation in an electric furnace with "black body" details in the temperature range of 300-750 K was measured. 2. To check the Stefan-Bolsman law, a graph of the dependence of radiation intensity on absolute temperature and distance was drawn.